Cellulose Nanofibers Extracted From Natural Wood Improve the Postharvest Appearance Quality of Apples - Wang, Yongxu; Zhang, Jing; Wang, Xinjie; Zhang, Tingting; Zhang, Fujun; Zhang, Shuai; Li, Yuanyuan; Gao, Wensheng; You, Chunxiang; Wang, Xiaofei; Yu, Kun (Frontiers in Nutrition, 2022)
To prolong the shelf life of perishable food with a simple and environmentally friendly postharvest preservation technology is one of the global concerns. This study aimed to explore the application value of biological macromolecule natural cellulose nanofibers (CNFs) in extending the postharvest fruit shelf life. In this study, 0.5% (wt%) CNFs were prepared from natural wood and coated on the surface of early-ripening apple fruits. After 10 days of storage at room temperature, the results revealed that the shelf life of apple fruits with CNF coating was significantly prolonged, and the fruit appearance quality improved. The invisible network structure of CNFs in the fruit epidermis was observed under an atomic force microscope (AFM). The gas chromatography and mass spectrometry (GC-MS) analysis showed that CNFs significantly promoted the formation of epidermal wax, especially fatty alcohols, during storage. In addition, the CNFs remarkably promoted the upregulation of genes related to the synthesis of cuticular wax of apple. In conclusion, this study provides an environmentally sustainable nanomaterial for post-harvest preservation of horticultural products, and also provides a new insight into the effect of CNFs on postharvest storage of apple fruits.